Micro and Nanomechanics, Volume 5 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics (Conference Proceedings of the Society for Experimental Mechanics Series,, 2018)
Micro-and Nanomechanics, Volume 5 of the Proceedings of the 2017 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the fifth volume of nine from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: MEMS & Energy Harvesting 1D & 2D Materials/Fabrication Micro/Nano Microscopy Techniques Nanomechanics Flexible & Stretchable Electronics Interfaces & Adhesion.